Determination the Lethal Dose50 (LD50 ) and Study of Acute Toxicity and Histopathological Effects of Glycosides Extract of Alhagi maurorum (Aqual) in Mice - AL-Jubory, Sadiyha Yasir (University of Thi-Qar Journal of Science, 2013)
This study was curried out on the extraction glycosides constituents of shoot and seeds of Alhagi maurorum (Aqual), determination LD50 and study histopathological effects of intestine, lungs ,liver and kidney in mice. The results exhibited acute toxicity with LD50 of shoot and seeds extract were 8333.333 and 7414.666 mg / kg respectively. Upon intraperitoneal administration in mice. The histopathological examination indicated that tested extract induced several histopathological changes in the mice such as degeneration, desquamation of epithelial cells, atrophy, destruction of villi, hemorrhage and necrosis in intestine .Pulmonary emphysema. Necrosis of some hepatocytes, hydropic degeneration, edema and there are scattered bile canaliculi in liver. Necrosis of some of renal tubules with atrophy in some other , as well asnecrosis of glomerulus with dilatation of bowman’s capsule, sloughing of epithelium lining of collecting tubules , as well as presence of completely fibrosis glomerulus .